The Advent of Islam In Indonesia and some Problems Related to the History of the Eraly Muslim Period - Baloch, N.A (Al-Jami'ah: Journal of Islamic Studies, 1980)
The Question often raised is: ‘whether Islam came to Indonesia from Arabia, the subcontinent of India, or China? Firstly, it is not a question of ‘or’ but of ‘and’: Muslims from these and other countries, but more so from the different part of the archipelago itself, contributed to the growth and development of Islam in what is now know as Indonesia. However, the first to bring Islam to the Indonesian shores, and further north to China were the early Arab Muslim. On the basis of available historical record, it would be reasonable to conclude that their intransit visits and temporary hats, first most probably on the coaslines of Sumatra, took place in the 1st century of Hijra (7th A.D), while the more frecuent and longer visit as well as permanent settlements came during the 2nd H./8th century A.D.